18F-sodium fluoride coronary uptake in patients with coronary artery bypass grafts. (25th November 2020) - Kwiecinski, J; Tzolos, E; Cadet, S; Adamson, P.D; Joshi, N; Dey, D; Berman, D.S; Newby, D.E; Dweck, M.R; Slomka, P.J
Abstract:  : 18F-Sodium fluoride (18F-NaF) positron emission tomography (PET) provides an assessment of active calcification (microcalcification) across a wide range of cardiovascular conditions including coronary artery disease, carotid and penile atherosclerosis, aortic and mitral valve disease, and abdominal aortic aneurysms. To date the significance of 18F-NaF uptake in patients with coronary artery bypass grafts (CABG) is unknown. We aimed to characterize 18F-NaF activity in CABG patients. We performed 18F-NaF PET (30-min long single bed position acquisition 1h after a 250mB injection of 18F-NaF) and coronary CT angiography in patients with multivessel coronary artery disease and followed them for fatal or non-fatal myocardial infarction over 42 [31, 49] months. On motion-corrected datasets we quantified the whole-vessel coronary 18F-NaF PET uptake (the coronary microcalcification activity (CMA)) by measuring the activity of voxels above the background (right atrium activity) + 2 * standard deviations threshold. All study subjects underwent a comprehensive baseline clinical assessment including evaluation of their cardiovascular risk factor profile with the SMART [Secondary Manifestations of Arterial Disease] risk score calculated, and the coronary calcium burden assessed with calcium scoring (CCS). Among 293 study participants (65±9 years; 84% male), 48 (16%) had a history of CABG. Although the majority 124/128 (97%) of coronary bypass grafts showed no uptake, 4 saphenous vein grafts presented with a CMA>0 (range: 2.5–11.5, Figure). While a similar proportion of patients with and without prior CABG showed increased coronary 18F-NaF uptake (CMA>0) (58.3% versus 71.4%, p=0.11) overall prior-CABG subjects had higher CMA (2.0 [0.3, 6.6] versus 0.6 [0, 2.7], p=0.001) and CCS (1135 [631, 2120] versus 225 [59, 542], p<0.001), respectively. In line with the differences in the calcification activity and the coronary calcium burden, the SMART risk scores were higher in CABG patients (23 [17, 28] versus 17 [12, 24], p=0.01), and these patients were also older (68±8 versus 64±8, p=0.01). Despite the aforementioned differences the incidence of myocardial infarction 5/48 (9%) versus 15/245 (6%) and MACE 6/48 (12%) versus 34/245 (14%) during follow-up between subjects with and without prior CABG was similar (p=0.44 and p=0.80, respectively). CABG patients have a higher coronary microcalcification activity on 18F-NaF PET than multivessel coronary artery disease patients without prior CABG. Despite evidence of higher 18F-NaF uptake there is no difference in outcome between these two groups. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): National Heart, Lung, and Blood Institute/National Institute of Health (NHLBI/NIH), British Heart Foundation